EFEKTIVITAS KERJA APARAT DESA (STUDI KASUS DI DESA PAKUUE DUA KECAMATAN TENGA KABUPATEN MINAHASA SELATAN) - RAMPI, JOHANES; RURU, JOORIE MARHAEN; PALAR, NOVIE (JURNAL ADMINISTRASI PUBLIK, 2019)
This research is done for the purpose of explaining the effectiveness of village personnel in the village ofPakuure two Tenga district of South Minahasa Regency in the study of public administration. The studyuses qualitative approach methods. The subject of this study amounted to 10 of the one occupying theresearch site so researchers took the conclusion to give the Kuisoner to the 10 subjects. . Data collectionusing interviews, observations, behavioral studies (documentation), while the analytical techniques usedare qualitative data analysis interaction models Miles and Huberman and Sugiono. The results of thestudy showed (a) more productivity is realized in the implementation of non-physical development and lessattention to the empowerment and strengthening of economic potential of the village community. (b) Thecreativity of the village apparatus is formed in establishing a working relationship with the district anddistrict governments as well as in conjunction with religious leaders but lack creativity in presenting thegovernment program to Improving people's living standards. (c) The working intensity of the villageapparatus is manifested in the division of work and seeks to optimally serve the community. However, theintensity of work produced as a form of occupational effectiveness has not been followed by theinvolvement and support of the community.Keywords: effectiveness, work effectiveness, village apparatus